Clinical significance of primary prophylactic pegylated‐granulocyte‐colony stimulating factor after the administration of ramucirumab plus docetaxel in patients with previously treated non‐small cell lung cancer. Issue 4 (11th March 2019) - Mouri, Atsuto; Kaira, Kyoichi; Shiono, Ayako; Yamaguchi, Ou; Murayama, Yoshitake; Kobayashi, Kunihiko; Kagamu, Hiroshi
Abstract : Whether primary prophylactic pegylated‐granulocyte‐colony stimulating factor (PEG‐G‐CSF) should be administered immediately after the initiation of ramucirumab plus docetaxel (DR) to prevent the occurrence of febrile neutropenia (FN) is unclear. Our retrospective study aimed to elucidate whether PEG‐G‐CSF could control the occurrence of FN as a result of DR in patients with previously treated non‐small‐cell lung cancer. Thirty‐three patients with previously treated non‐small‐cell lung cancer who had received DR were eligible for our analysis. Of the 33 patients, 29 received prophylactic PEG‐G‐CSF immediately after DR, but none developed FN. However, FN was observed in 2 (50%) of the 4 patients that were not administered PEG‐CSF. The overall response and disease control rates in the 29 patients with prophylactic PEG‐GSF were 31% and 62%, respectively. The median progression‐free and overall survival rates of the patients with and without prophylactic PEG‐GSF were 177 and 163 days ( P = 0.20), and 628 and 274 days ( P = 0.13), respectively. Primary prophylactic PEG‐G‐CSF suppressed the occurrence of FN secondary to the administration of DR.